Between Orthodoxy and Heresy in the Pedagogy of Religion. The Hermeneutic and Aesthetic Inspirations by the Thought of Gianni Vattimo, Luigi Pareyson and Erika Fischer-Lichte - Humeniuk, Monika (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2022)
The subject of the study is a project of ‘weak’ pedagogy of religion. This project is inspired by post-metaphysical thought of Gianni Vattimo. Poor ontology and radical hermeneutics become a strategy of opening the pedagogy of religion to heresy, i.e. ambiguity, polyphony of interpretation of texts, artefacts, and religious practices. Thanks to this, the traditional pedagogy of religion gains the possibility of seeking inspiration for itself on new, non-theological borderlines of aesthetics and performatics.Two examples of such references are mentioned in the study: Luigi Pareyson’s aesthetics of formativity and Erika Fischer-Lichte’s aesthetics of performativity. They show interesting examples of progression from orthodoxy to heresy in the ‘weak’ pedagogy of religion.
Keywords: radical hermeneutics; Gianni Vattimo; weak thought; Religious education; Luigi Pareyson; aesthetics of formativity; aesthetics of performativity; Erika Fischer-Lichte